Leisure activities and travel habits of college students in the light of a survey - Mosonyi, Attila; Könyves, Erika; Fodor, Ibolya; Müller, Anetta (Applied Studies in Agribusiness and Commerce, 2013)
In our article we deal with leisure activities and travel habits of 150 college students from Szolnok. We have analyzed the relationship between the frequencies of watching TV, that is: the time spent watching TV and doing sports. Furthermore, we have also investigated the frequencies of travels, and main motives of choosing travel destinations. We have found that college students have several hours of leisure time daily. Among the recreational activities, the ones that occurred predominantly are watching TV, doing sports, and travelling. It is interesting to note that the relationship between the frequency of watching TV and doing sports has not been significant while the relationship between watching TV occasionally and doing regular physical activity has turned out to be significant. Students who play sports for 1-2 hours a day spend significantly less time in front of the TV compared to their peers who do not do sports. 92% of the students travel at least once a year. The participants of youth tourism are quite price-conscious. In choosing travel destinations favorable prices play an important role.